2019
DOI: 10.3389/fphar.2019.00823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molecular Hydrogen on Methamphetamine-Induced Neurotoxicity and Spatial Memory Impairment

Abstract: Methamphetamine (METH) is a highly addictive stimulant, and METH exposure can induce irreversible neuronal damage and cause neuropsychiatric and cognitive disorders. The ever-increasing levels of METH abuse worldwide have necessitated the identification of effective intervention strategies to protect the brain against METH-induced neurotoxicity. The protective effects of molecular hydrogen on oxidative stress and related neurodegenerative diseases have been recently elucidated. Herein, we investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The water maze consisted of an off-white circular pool (80 cm in diameter) with the upper part surrounded by a 40 cm-high Perspex wall and filled with water at 25 ± 1°C [ 29 ]. The circular pool was segmented into four quadrants and enclosed in a curtain.…”
Section: Methodsmentioning
confidence: 99%
“…The water maze consisted of an off-white circular pool (80 cm in diameter) with the upper part surrounded by a 40 cm-high Perspex wall and filled with water at 25 ± 1°C [ 29 ]. The circular pool was segmented into four quadrants and enclosed in a curtain.…”
Section: Methodsmentioning
confidence: 99%
“…MA exposure can induce irreversible neuronal damage and cause neuropsychiatric and cognitive disorders. 45,46 MA may become addicted once taken, and addictive symptoms may appear after short-term use. Long-term or highdose use of MA causes abnormalities in the structure, chemistry, and function of brain, resulting in some associated medical complications and fatalities.…”
Section: Protein−protein Interactions Between Trkb and Cammentioning
confidence: 99%
“…Molecular hydrogen, as a novel healthcare product for a wide range of diseases, has recently become increasingly popular because of its unique anti-oxidative capability of selectively scavenging highly cytotoxic oxygen radicals and its anti-inflammatory properties ( Qi et al, 2021 ). Our previous studies have revealed that molecular hydrogen delivered by ad libitum hydrogen-rich water (HRW) consumption significantly inhibited METH-induced spatial memory impairment in the Barnes and Morris water maze tests ( Wen et al, 2019 ). In addition, hydrogen-rich saline (HRS) injections attenuated symptoms of low dose METH-induced behavioral sensitization ( Wen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%